Analysis of Mathematical Representation Capabilities in Geometry Materials Assisted by Geogebra Applications - Hidayat, Yandi Wahyu; Pramuditya, Surya Amami; Aminah, Neneng (IndoMath: Indonesia Mathematics Education, 2023)
This study aims to determine the ability of mathematical representation of students in geometry material after learning with the help of GeoGebra. This research is motivated by students' difficulty in interpreting geometric shapes. This research is qualitative research with a descriptive approach. The subjects in this study were 3 (three) class XII students who had obtained three-dimensional material with the help of GeoGebra applications. Researchers carry out the data collection process by providing mathematical representation ability test questions, conducting interviews, and taking documentation. The data obtained in this study were analyzed using specialized triangulation-checking techniques. Based on the results of data analysis and the effects of interviews with all research subjects, it can be concluded that learning geometry with the help of GeoGebra applications can improve mathematical representation capabilities. Three mathematical representation abilities, namely visual representation, equation or expression, and written words or texts, are possessed by students after learning geometry with the help of GeoGebra applications.